Combined Treatment and Power Generation from fertilizer waste water Using Microbial Fuel Cell - Onuabuchi Azunna; Akuma Oji; Obumneme O. Okwonna; Nnadikwe Johnson (Journal Majelis Paspama, 2025)
The increasing environmental problem of fertilizer wastewater associated by high loads of pollutants, necessitates the microbial fuel cell innovative treatment technologies that not only mitigate pollution but also generate power. This research investigates the dual-purpose application of Microbial Fuel Cells (MFCs)for thecombined treatment and power generation from fertilizer wastewater, offering a sustainable solution that integrates wastewater remediation with renewable energy production. The study explores the design, optimization, and performance evaluation of single- and dual-chamber microbial fuel cell systems using urea fertilizer wastewater as substrates. Key parameters including chemical oxygen demand (COD) removal efficiency, dissolve Oxygen, % ammonia and %Urea reduction, Current and power density were monitored under varying operational conditions (e.g., electrode materials, pH, temperature, retention time). Advanced electrochemical and microbiological techniques were employed to characterize the anodic biofilms and understand the dynamics of the electroactive microbial communities driving the simultaneous biodegradation and electron transfer processes. Result demonstrate that microbial fuel cell can achieve treatment of fertilizer wastewater (COD > 80%, ammonia > 70%) while generating stable output outputs up to 0.66MA and voltage of 0.91V, depending on reactor configuration and substrate concentration. The experimental result shows that Ammonia fertilizer plant effluent is one of the best substrates for energy generation in mfc. The integration of bio electrochemical systems with fertilizer industry effluents not only enhances wastewater treatment efficiency but also contributes to decentralized. This thesis provides a comprehensive analysis of the feasibility, challenges, and scalability of MFC technology for agro-industrial applications, contributing to the global pursuit of circular economy models and sustainable wastewater-energy nexus solutions.